An evaluation study of the experience of the preparatory year for medical faculties at Tishreen University and the prospects for its future development "A field study from the point of view of a sample of students" - زمرد أميرة; بوبو منذر; أمون رامي; أيوب رنيم (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The aim of the current research is to investigate the reality of the preparatory year at Tishreen University in terms of academic courses, teaching methods and evaluation methods…etc), and to measure the degree of students’ satisfaction with the components of the experience in general (curricula, teacher performance, evaluation...etc). It also aimed to monitor the strengths and weaknesses of the preparatory year in an effort to present proposals for their development, from the point of view of a sample of students who went through this experience. The method was used descriptive, and the tool was a questionnaire, which was applied to (566) students (second and fifth years of medicine, dentistry and pharmacy, first year of medical engineering. The results of the research confirmed that the most important subjects are: physiology, anatomy, languages, genetics and cell biology; While the less important subjects are: medical statistics and history of medicine, and that the subjects are interconnected and their content is repetitive to a moderate degree, and that the subjects of physiology and anatomy are the most useful subjects for the student’s current specialization, and that (60.25%) of students have undergone strengthening courses in institutes outside the university, and the main reason is Therefore: the content of the subjects is new, huge and difficult for them, and that the majority of students decided to use the automated exam as a method of theoretical assessment, and that all assessment methods are used in the preparatory year on the practical side, and they are satisfied with it to a moderate degree, and they are moderately satisfied with the practical side, and it serves the specialization High level human medicine. The degree of students’ satisfaction with the performance of the preparatory year teachers is medium, the preparatory year is low, the sorting method is high, and the administrative services are medium, and that the preparatory year contributes to a medium degree in directing students to a specific specialization. The most important positives of the preparatory year were: its definition of medical specialties and the fairness of the triage system, and the most prominent negative: the content of the courses is not good and it is a stressful year for the student, and the most important proposals: developing the content of the courses and amending the two systems: screening and evaluation. The highest percentage of students (62.54%) saw the necessity of canceling the preparatory year.